eRNAs Identify Immune Microenvironment Patterns and Provide a Novel Prognostic Tool in Acute Myeloid Leukemia - Jiang, Ziming; Long, Junyu; Deng, Kaige; Zheng, Yongchang; Chen, Miao (Frontiers in Molecular Biosciences, 2022)
Background Enhancer RNAs (eRNAs), the small non-coding RNAs transcribed from enhancer regions, play essential roles in tumorigenesis. However, the landscapes of eRNAs in acute myeloid leukemia (AML) and the potential roles in tumor microenvironment (TME) remain unclear. Method Gene expression data collected from The Cancer Genome Atlas (TCGA) databases combined with Histone ChIP-seq revealed the comprehensive landscapes of eRNAs. The single-sample gene set enrichment analysis algorithm and ESTIMATE was applied to enumerate immune cells infiltration and tumor purity. Results Most prognostic eRNAs were enriched in immune-related pathway. Two distinct patterns, immune-active and immune-resistant subtype, were identified in AML and discriminated current clinicopathologic features. We further developed an eRNA-derived score (E-score), which could quantify immune profiles and predict response to immune-checkpoint inhibitor (ICI) treatment. Finally, we established a prognostic nomogram combining E-score and other clinical features, which showed high predictive accuracy. Conclusion In this study, we obtained a systemic understanding of the eRNAs’ roles in modulation of TME diversity and complexity. And our E-score model provided the first predictive model for ICI therapy in AML.